Degradation of the Stigma of Prison as a Criminal School Through Supervised Sentence as an Alternative to Imprisonment - Rohmat Rohmat; Milda Istiqomah; Nurini Aprilianda (Indonesian Journal of Criminal Law Studies, 2024)
With the development of penal theory, the retributive approach to punishment is increasingly seen as misaligned with the needs of society. As a result, there is a recognized need for legal provisions that reflect societal values and emphasize punishment goals that strengthen the community. Prison sentences often lead to issues such as overcrowded facilities and a failure to meet punishment goals. Additionally, many convicts tend to become recidivists after completing their sentences in correctional institutions, reinforcing the stigma of prisons as "criminal schools." The issues to be examined include: a) how are conditional sentences regulated in Law Number 1 of 1946?; and b) how is the policy of supervision sentences as an alternative to imprisonment in degrading the stigma of prison as a criminal school? The research was conducted using a normative method, with a legislative approach. The legal materials used include both primary and secondary legal materials, which were analyzed using deductive analysis techniques. Under the old Penal Code, conditional sentences did not involve immediate imprisonment; instead, the convicted person was given the opportunity to prove their ability to live as a good citizen during a specified probation period. In contrast, the National Penal Code introduces alternatives to prison sentences, such as supervision sentences. These supervision sentences in the National Penal Code serve as an extension of conditional sentences, placing greater emphasis on more intensive and structured supervision. The placement of convicts outside correctional institutions is considered the primary penal system, with the imposition of supervised sentences based on general and specific requirements. In future implementation, an ideal model for the execution of this supervisory sentence is required.